PENGARUH EARNINGS DAN ARUS KAS TERHADAP RETURN SAHAM TERKAIT DENGAN SIKLUS HIDUP PERUSAHAAN (Studi pada Perusahaan Manufaktur yang Terdaftar di BEJ Tahun 2001 - 2005) - Bayu Giri Prakosa (Akademi Akuntansi YKPN Yogyakarta, 2012)
The purpose of this study is to find whether the differences in life-cycle stages affect the usefulness of accounting performance measures, such as earnings and cash flow. Corporate life cycle consists of four stages: start-up, growth, mature and decline. Using financial data of companies listed in Jakarta Stock Exchange (JSE) from periods of 2001 to 2005, classified by pooled cross-sectional method, and tested by double regression - Ordinary Least Square (OLS) model, the study finds that stock return of start-up, growth, mature, and decline firms are influenced by earnings per share (EPS). Cash flows from finance activities have relevance to stock return in the decline stage. Overall, this study provides evidence that corporate life cycle influence the incremental valuerelevance of earnings and cash flows.Keywords: Earnings, Cash Flows, Corporate life cycle, Stock Return and Value-relevance.